Frontline brentuximab vedotin-based therapy for newly diagnosed classical Hodgkin lymphoma: a meta-analysis of randomized controlled trials - Yang, Yue; Liu, Shu-rong; Wang, Li; Zhang, Rui; Xie, Jing (Frontiers in Oncology, 2025)
BackgroundBrentuximab vedotin (BV), an anti-CD30 antibody-drug conjugate, has established efficacy in relapsed/refractory Hodgkin lymphoma (HL), yet its role as frontline therapy for newly diagnosed classical HL requires systematic evaluation.MethodsWe conducted a meta-analysis of randomized controlled trials (RCTs) compared BV-based versus conventional non-BV-containing regimens (namely, classical chemotherapeutic regimens) in previously untreated classical HL patients, assessing progression-free survival (PFS), PET metabolic responses (interim PET-2 negativity and end-of-treatment complete response), and safety profiles (grade ≥3 adverse events [AEs], including febrile neutropenia, peripheral neuropathy, and secondary malignancies).ResultsPooled data from four RCTs (N = 3591 patients) demonstrated significant PFS improvement with BV-based regimens (HR: 0.58, 95% CI: 0.44 to 0.77, P < 0.001), with consistent benefits across subgroups stratified by disease stage, gender, age, and International Prognostic Score (IPS). Although interim PET-2 negativity rates showed only a non-significant trend favoring BV (RR: 1.02, 95% CI: 0.99 to 1.04, P = 0.286), end-of-treatment complete metabolic response rates were significantly higher (RR: 1.03, 95% CI: 1.00 to 1.06, P = 0.024). Safety analyses revealed comparable incidences of grade ≥3 AEs between groups (RR: 1.05, 95% CI: 0.80 to 1.37, P = 0.739), with no increased risk of peripheral neuropathy or secondary malignancies.ConclusionsOur meta-analysis demonstrates that incorporation of BV into frontline therapy for classical HL provides significant PFS benefits and improved end-of-treatment metabolic responses, with manageable toxicity. These findings support BV-based regimens as a promising frontline therapeutic strategy in classical HL, though extended follow-up is required to evaluate long-term survival outcomes.